Rola państwa w gospodarce rynkowej : Stany Zjednoczone, Niemcy, Japonia - Dobrzański, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The role of the government in the economy is one of the basic problems of economic theory and policy. Economic activity of the government and its impact on the economic process are one of the most controversial economic issues. Nowadays, there is no socio-economic theory acceptable to all economists that would describe the problem of government activity. The main goal of the article is to present the role of government in market economy system. For this purpose, general theory of the role of government in market economy is described, and the differences and similarities between United States, Germany and Japan are presented. The article also presents an assessment of government activity in the studied countries, inter alia The Global Competitiveness Report, World Competitiveness Report and Index of Economics Freedom
Keywords: system gospodarki rynkowej; rząd; efektywność rządu; konkurencyjność